External memory aids for memory problems in people with multiple sclerosis: a systematic review - Goodwin, Rachel; Lincoln, Nadina; das Nair, Roshan; Bateman, Andrew (Taylor & Francis, 2015)
Approximately 40-60% of people with multiple sclerosis (MS) have memory problems, which adversely impact on their everyday functioning. Evidence supports the use of external memory aids in people with stroke and brain injury, and suggests they may reduce everyday memory problems in people with MS. Previous reviews of people with MS have only evaluated randomised trials; therefore this review included other methodologies. The aim was to assess the efficacy of external memory aids for people with MS for improving memory functioning, mood, quality of life, and coping strategies. Seven databases were systematically searched. Intervention studies that involved training in the use of external memory aids, e.g., personal digital assistants, with at least 75% of people with MS, were included. Based on study design, quality was rated with the SCED or PEDro scale. Nine studies involving 540 participants were included. One single case experimental design (mean of 8 on SCED scale) and eight group studies (mean of 5 on PEDro scale) were included. One study reported a significant treatment effect on subjective memory functioning, two on mood, and two on coping strategies. There is insufficient evidence to support or refute the effectiveness of external memory aids for improving memory function in people with MS.